Sulfur Atoms Bridging Few‐Layered MoS2 with S‐Doped Graphene Enable Highly Robust Anode for Lithium‐Ion Batteries. Issue 23 (22nd September 2015) - Wang, Xiaolei; Li, Ge; Seo, Min Ho; Hassan, Fathy M.; Hoque, Md Ariful; Chen, Zhongwei
Abstract : Sulfur atoms covalently bonded to graphene and efficiently bridging few‐layered MoS2 and graphene enable a MoS2 /SG composite with excellent Li + storage capacity and remarkably long cycling stability. Such composite materials hold great promise in next‐generation rechargeable lithium‐ion batteries.